PMR (PHARMACY MEDICAL RECORD): REKAM MEDIS PENGOBATAN APOTEK BERBASIS WEBSITE - Rasyid Burhanudin Fahmi, Rafiqa Maharani Putri Siregar, Rahmat Rinaldy, Siska Hariyanti, Dyah Palupi (STMIK Sinar Nusantara, 2017)
A lot of medication error toward patient due to pharmacist lacks of knowledge on the patient’s medical record and previously consumed medicines list. This may cause harm to the patient. Not to mention that most pharmacists does not know about the allergy the patient may have to certain medicines. Medical record is a file containing notes and documents that concern identity, examination, treatment, action, and other services that have been given to the patients. The aim of this research is to minimize errors in the administration of medicines toward patients and to maximize the role of pharmacists in monitoring public health by collecting society’s medical records using PMR applications (Pharmacy Medical Record). PMR is an information system based application that stores medical records of patients that can be used by health workers particularly pharmacists to take the right decision in supporting the health of the patient. This research is a non-experimental descriptive research with quantitative approach. Samples were taken in the region of Apotek Akmal Sehat and Apotek Sondakan of Surakarta. The results showed that PMR can assist the pharmacist in making decisions that are logical, right and focusing on the quality of the health of patients by monitoring the medical records of medicines.Therefore, the application of PMR based information system qualifies as a provider of data with quality which is accurate, right on time, and relevant. Keywords: Information System, Medication Error, Medicine Medical Record, Pharmacist, PMR